An investigation into the importance of considering protection performance during power system out-of-step conditions - Van Eyssen, Juanita (Department of Electrical Engineering, 2016)
The performance of power system protection is affected by out-of-step conditions in that system. Protection relays such as distance relays may detect an out-of-step condition and consequently operate to trip unfaulted lines. The tripping of unfaulted lines interrupts supply to loads and exacerbates an already existing stability problem. To prevent distance-relay operation during out-of-step conditions, distance protection can incorporate out-of-step blocking protection. The purpose of the out-of-step blocking protection is to detect an out-of-step condition and, upon detection, block distance-relay operation. In the research the following were investigated: 1) The effect of out-of-step conditions on distance-protection performance 2) The performance of distance protection incorporating out-of-step blocking protection, during out-of-step conditions. A nine-bus IEEE benchmark network was chosen for the purposes of the research. The nine-bus network is representative, simple and small. It is a benchmark which is often used in comparative studies in the power system field. The nine-bus network data taken from reference [22] (see Table 3.1 in Chapter 3) were consistently used for every study done. Mathematical protection models representing the behaviour of distance protection incorporating out-of-step blocking protection were modelled in such a way as to simulate the protection of every line in the nine-bus network. These models were included in the power system model representing the nine-bus network. Two types of stability studies were done to investigate protection performance: a dynamic-stability study and a transient-stability study. IV In modelling the protection in the stability studies, it was found that a cascade effect of switching unfaulted lines can occur due to relay operation. Results also show that distance-protection performance improves with the application of out-of-step blocking protection. The research covers the following topics: 1) Dynamic stability 2) Transient stability 3) Distance protection 4) Out-of-step blocking protection results are discussed. An important conclusion reached is the need to take protection performance into account in routine stability studies. It will be shown that this may change the outcome of a stability study. For the sake of completeness, suggestions are made for further research.